Protein Biomarker Identification for the Discrimination of Brucella melitensis Field Isolates From the Brucella melitensis Rev.1 Vaccine Strain by MALDI-TOF MS - Kornspan, David; Brendebach, Holger; Hofreuter, Dirk; Mathur, Shubham; Blum, Shlomo Eduardo; Fleker, Marcelo; Bardenstein, Svetlana; Al Dahouk, Sascha (Frontiers in Microbiology, 2021)
Brucella melitensis Rev.1 is a live attenuated vaccine strain that is widely used to control brucellosis in small ruminants. For successful surveillance and control programs, rapid identification and characterization of Brucella isolates and reliable differentiation of vaccinated and naturally infected animals are essential prerequisites. Although MALDI-TOF MS is routinely applied in clinical microbiology laboratories for the diagnosis of brucellosis, species or even strain differentiation by this method remains a challenge. To detect biomarkers, which enable to distinguish the B. melitensis Rev.1 vaccine strain from B. melitensis field isolates, we initially searched for unique marker proteins by in silico comparison of the B. melitensis Rev.1 and 16M proteomes. We found 113 protein sequences of B. melitensis 16M that revealed a homologous sequence in the B. melitensis Rev.1 annotation and 17 of these sequences yielded potential biomarker pairs. MALDI-TOF MS spectra of 18 B. melitensis Rev.1 vaccine and 183 Israeli B. melitensis field isolates were subsequently analyzed to validate the identified marker candidates. This approach detected two genus-wide unique biomarkers with properties most similar to the ribosomal proteins L24 and S12. These two proteins clearly discriminated B. melitensis Rev.1 from the closely related B. melitensis 16M and other B. melitensis field isolates. Based on our results, we propose MALDI-TOF MS profiling as a rapid, cost-effective alternative to the traditional, time-consuming approach to differentiate certain B. melitensis isolates on strain level.